2002
DOI: 10.1054/jhsb.2002.0828
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Review of Open Central Slip Laceration Repair and Rehabilitation

Abstract: A prospective review was carried out to evaluate the outcome of surgically repaired open central slip (zone III) injuries which were treated with 3 weeks of proximal interphalangeal joint immobilization within a cylinder splint and then with 3 weeks of controlled mobilization within a Capener coil splint. Thirty-one fingers in 27 patients were assessed by the same independent therapist. All fingers achieved an excellent or good recovery with a mean proximal interphalangeal joint flexion of 94 degrees (range 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
1
11
0
2
Order By: Relevance
“…First, management of the central slip injury requires splinting because immediate ROM may not allow adequate healing. 12 The central slip injury could have been overlooked in light of the more severe injury to the epiphysis. The desire to get patients moving to avoid stiffness could have been detrimental to the second and more subtle injury.…”
Section: Discussionmentioning
confidence: 99%
“…First, management of the central slip injury requires splinting because immediate ROM may not allow adequate healing. 12 The central slip injury could have been overlooked in light of the more severe injury to the epiphysis. The desire to get patients moving to avoid stiffness could have been detrimental to the second and more subtle injury.…”
Section: Discussionmentioning
confidence: 99%
“…Pratt et al described a regime of immobilisation of the PIP joint in a cylinder splint for three weeks followed by a Capener dynamic splint. 27 Several studies had shown the benefits of dynamic splinting, 23,28,29 early active mobilisation for extensor tendon, 30,31 and early active mobilisation for central slip injury. 6,7 O'Dwyer and Quinton used a combination of initial rigid splintage followed by a dynamic Capener splint starting between day 10 to day 14 and reported that 88% of patients had excellent or good results after six months.…”
Section: Discussionmentioning
confidence: 99%
“…His 27 patients (31 fingers) demonstrated good to excellent results, but 5 fingers had extension deficits. 29 Zone IV Similar to zone II injuries, zone IV injuries are most often secondary to lacerations. Because the tendon is flat and wraps around the proximal phalanx at this level, injuries are frequently partial.…”
Section: Zone IIImentioning
confidence: 99%